Sikap Siswa Sekolah Dasar Terhadap Pelajaran Matematika: Attitudes of the Students Towards Mathematics Lessons - Nur Ismiyati (De Fermat : Jurnal Pendidikan Matematika, 2020)
This study aims to see students' attitudes towards mathematics in third grade Public Elementary School students in Gunung Bahagia Village, Balikpapan. The subjects in this study were 174 students. Subject selection was done randomly. The technique of using data is by providing the first questionnaire to adapt from Tezer & Ozcan to a scale using facial expressions because students still have difficulty expressing attitudes in written form. The result of this research is that the general attitude of students towards mathematics is neutral, which means that they are normal towards mathematics.